2019
DOI: 10.1167/iovs.18-25750
|View full text |Cite
|
Sign up to set email alerts
|

Visual Cortical Plasticity in Retinitis Pigmentosa

Abstract: PURPOSE. Retinitis pigmentosa is a family of genetic diseases inducing progressive photoreceptor degeneration. There is no cure for retinitis pigmentosa, but prospective therapeutic strategies are aimed at restoring or substituting retinal input. Yet, it is unclear whether the visual cortex of retinitis pigmentosa patients retains plasticity to react to the restored visual input. METHODS. To investigate short-term visual cortical plasticity in retinitis pigmentosa, we tested the effect of short-term (2 hours) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 84 publications
(114 reference statements)
1
14
0
Order By: Relevance
“…As shown in Figure 8 , however, we used our raw data from baseline and postpatching to directly compute the effect size to be more precise. Also, many studies have a smaller sample size than ours ( n = 15), so the reported effect size might have been more prone to a few outliers who displayed an exceptionally large change in sensory eye balance ( Bai, Dong et al, 2017 ; Binda, Kurzawski et al, 2018 ; Binda & Lunghi, 2017 ; Kim, Kim et al, 2017 ; Lo Verde, Morrone et al, 2017 ; Lunghi, Burr et al, 2011 ; Lunghi, Burr et al, 2013 ; Lunghi, Galli-Resta et al, 2019 ; Ramamurthy & Blaser, 2018 ; Wang, McGraw et al, 2020 ). In addition, although applying a diffuser to one eye is a common method to monocularly deprive its visual input, the methods of monocular deprivation can differ across studies.…”
Section: Discussionmentioning
confidence: 73%
“…As shown in Figure 8 , however, we used our raw data from baseline and postpatching to directly compute the effect size to be more precise. Also, many studies have a smaller sample size than ours ( n = 15), so the reported effect size might have been more prone to a few outliers who displayed an exceptionally large change in sensory eye balance ( Bai, Dong et al, 2017 ; Binda, Kurzawski et al, 2018 ; Binda & Lunghi, 2017 ; Kim, Kim et al, 2017 ; Lo Verde, Morrone et al, 2017 ; Lunghi, Burr et al, 2011 ; Lunghi, Burr et al, 2013 ; Lunghi, Galli-Resta et al, 2019 ; Ramamurthy & Blaser, 2018 ; Wang, McGraw et al, 2020 ). In addition, although applying a diffuser to one eye is a common method to monocularly deprive its visual input, the methods of monocular deprivation can differ across studies.…”
Section: Discussionmentioning
confidence: 73%
“…34). In a separate work by our group, we found that RP patients with sparing of the central visual field have increased visual plasticity, stronger in patients with greater deficits, suggesting that cortical gating might be active throughout the evolution of the disease35 and it might be the consequence of cross-modal (or maladaptive) plasticity.…”
Section: Discussionmentioning
confidence: 74%
“…Although general alterations of brain activity have been described in individuals with RP [27][28][29] and animal models [30,31], the impact of retinal degeneration on cortical circuits is largely unknown. Only recently, it has been shown that the adult brain of RP patients retains a good level of short-term plasticity [32], and we have reported that visual cortical circuits in rd10 mice preserve their capability of input-dependent remodeling until an advanced stage of retinal damage [33].…”
Section: Introductionmentioning
confidence: 89%